Constraining chameleon models with cosmology. Issue 7 (16th June 2014) - Lombriser, Lucas; Battye, Richard; Goobar, Ariel; Weller, Jochen
<x xml:space="preserve">Abstract</x> Chameleon fields may modify gravity on cluster scales while recovering general relativity locally. This article reviews signatures of chameleon modifications in the nonlinear cosmological structure, comparing different techniques to model them, summarising the current state of observational constraints, and concluding with an outlook on prospective constraints from future observations and applications of the analytic tools developed in the process to more general scalar‐tensor theories. Particular focus is given to the Hu‐Sawicki and designer models of <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh112zzn19" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />f(R)</alternatives> gravity. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>